Liberation historiography : African American writers and the challenge of history, 1794-1861 - Ernest, John (University of North Carolina Press, 2004)
As the story of the United States was recorded in pages written by white historians, early-19th-century African American writers faced the task of piecing together a counterhistory. Here, John Ernest demonstrates that African Americans created a body of writing in which the spiritual, the historical and the political are inextricably connected.